10–5 Animal tissue models – a beginner's perspective. (17th November 2017) - Major, D; Peck, J; Websdale, D; Clappison, E; Wright, D; Purva, M
Abstract : Introduction: The HILS courses team were tasked with running a wet lab workshop as part of a Regional Tech Themed meeting organised by Health Education England in April 2017. When starting out in 2011 the team were challenged with learning how to create and set up models for the surgical training courses taking place within the centre. Six years on the team have acquired a vast array of skills in the creation of the models through self learning and observing at other centres. The workshop provided opportunity to share the knowledge and resources with other individuals interested in setting up their own models. Methods: The courses team reflected on the level of expertise required for the animal tissue models. In addition to learning the models themselves the team soon realised that it was equally as important to follow animal tissue policies in terms of purchasing the meat, storage through to disposal. The team developed a presentation for individuals to provide an overview from a beginner's perspective. Models range from using low fidelity custard abscesses and crushed foxes mints for debris to higher fidelity models dependant on the course. Prepping was discussed in terms of the equipment needed such as sharps bins, gloves, aprons, etc. Individual's were reminded that when prepping, handling and disposing of models, they should wear aprons and gloves themselves. There are many considerations into the safety and regulations of animal tissue, the team purchase from Medical Meats based in Rotherham, which is a trusted provider of meat used for clinical procedures; we are not able to bring in meat from a supermarket or any other source. A log of animal tissue has to be kept to detail where it was purchased from, how it was stored and disposed of, this is to ensure that the meat can be tracked back should there be any issues with it. We work in partnership with the provider who is able to meet our needs in designing more advanced models such as sewing in polyps. Results: The workshop was well attended and provided opportunity for discussion with other clinical skills centre staff across the region, sharing advice and knowledge as well as meeting new colleagues with whom we could network with to ensure that best practice is adhered to. Conclusion: The animal tissue models enhance the realism of surgical courses for our surgical trainees. The animal tissue is much more human like than models and manikins. Manikin replacement parts can be quite an expense therefore it is much more economical to use animal tissue for procedures where incisions and dissection is required. The team are now able to provide a beginners guide to animal tissue models and share knowledge/resources/best practice with others. The team aim to set up courses in the future to allow colleagues across the region to attend and learn the required skills.